The Influence Of Store Atmosphre Oh!Some Store Mediated By Positive Emotion On Impulse Buying Generation Z In Surabaya - Osama Rachmad Ramadhani; Muhammad Rizky Ramadhan (Finance : International Journal of Management Finance, 2025)
This study explores the effect of store atmosphere on impulse buying among Generation Z in Surabaya, mediated by positive emotion, in the context of Oh!Some—a rebranded specialty store targeting young consumers. The research aims to empirically examine whether an engaging retail environment can stimulate spontaneous purchase behavior through emotional responses. A quantitative method was employed using a structured online questionnaire distributed to 200 Generation Z consumers who had shopped at Oh!Some stores in Surabaya. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) using SmartPLS 4 was used for data analysis. The findings reveal that store atmosphere significantly and positively influences both impulse buying and positive emotions. Moreover, positive emotion serves as a significant mediator between store atmosphere and impulse buying. These results confirm the applicability of the Stimulus-Organism-Response (S-O-R) theory, demonstrating that environmental stimuli (store atmosphere) trigger internal emotional reactions (positive emotion), which lead to behavioral responses (impulse buying). The implications suggest that retailers must strategically manage physical and emotional aspects of their store environments to enhance emotional connection and impulse purchasing among young consumers. This research contributes to consumer behavior literature by reinforcing the mediating role of emotions in modern retail settings.